Review Efisiensi Bahan Bakar Solar Fuel Oil (SFO) dan Liquefied Natural Gas (LNG) Terhadap Kinerja Boiler Pembangkit Listrik Tenaga Uap (PLTU) - Yusuf Afrizal; Dani Rusirawan (TIN: Terapan Informatika Nusantara, 2026)
Fuel is a primary component in the operational system of Steam Power Plants (PLTU) because it functions as the main source of thermal energy used to heat water in the boiler to produce high-pressure steam. The generated steam is then directed to the steam turbine to rotate the turbine blades, enabling the generator to operate and produce electrical energy. The performance and efficiency level of a power plant are highly influenced by the type of fuel used in the boiler combustion process. Therefore, selecting an appropriate fuel type becomes an important factor in improving the efficiency of power generation systems and optimizing energy utilization. This study aims to analyze the comparison of efficiency levels between the use of Solar Fuel Oil (SFO) and Liquefied Natural Gas (LNG) in the boiler system of a steam power plant. The method used in this research is a literature review by collecting and analyzing data from previous studies related to the use of oil-based and gas-based fuels in steam power plants. The collected data are then compared to identify differences in the energy performance produced by each type of fuel. The results of the study indicate that the use of Solar Fuel Oil (SFO) produces an efficiency value of approximately 36.45% with a power output of around 0.30175 MW. Meanwhile, the use of Liquefied Natural Gas (LNG) demonstrates better performance, with an efficiency value reaching 55% and a power output of approximately 200 MW. These differences indicate that gas-based fuel has a more optimal combustion capability and produces thermal energy more efficiently compared to oil-based fuel.